Education on Bullying Prevention for Junior High School Students at Muhammadiyah 5 Padang - Ramadani, Mery; Markolinda, Yessy; Augia, Trisfa; Nurliza, Okta; Salsabila (Warta Pengabdian Andalas, 2026)
According to a 2019 survey by United Nations Education, Scientific, and Cultural Organization (UNESCO), bullying occurs in children worldwide. Globally, more than 30 percent of students aged 13 to 15 regularly experience bullying. Bullying can cause anxiety and fear in adolescents, disrupt concentration in school, and encourage them to avoid the school environment. Bullying problems that occur in schools require preventive intervention. The goal is to prevent this bullying practice from continuing or escalating into more extreme actions. Interventions in the form of education and training are an initial effort to convey a message to adolescents, individuals, or groups about the dangers of bullying. Community service activities at Muhammadiyah 5 Junior High School in Padang City aimed to increase adolescents' knowledge of bullying prevention. The implementation consisted of four stages: problem analysis, preparation, implementation, and evaluation of activities. The average pretest knowledge level increased from 58.47 to 84.02 (posttest) after the education was provided to 72 students. This activity has been proven to increase students' and the school community's insight and understanding of bullying. For the program's sustainability, it is hoped that the school will be involved and committed to regular bullying eradication activities. A sustainable program will increase anti-bullying awareness in schools.